Chain packing in the noncrystalline region of deuterated UHMWPE: A solid-state 2H and 13C NMR study. (November 2017) - Zhang, Ran; Xiao, Ting; Graf, Robert; De-Boer, Ele; Verhoef, Rene; Kentgens, Arno; Yang, Guang; Rastogi, Sanjay; Yao, Ye-Feng
Graphical abstract: Highlights: Chain packing influences on the noncrystalline conformation and dynamics of PE. The geometry and frequency of noncrystalline segmental motion revealed by 2 H NMR. Chain motions and conformation statistics in the noncrystalline regions of PE. Abstract: Chain packing in the non-crystalline region of a semi-crystalline polymer is strongly influenced by the crystallization conditions. Using a single-site catalytic system, deuterated Ultra High Molecular Weight Polyethylenes (UHMW-PEs) are synthesized and the chain topology of the noncrystalline region is investigated by solid-state NMR. The variability in chain packing within the noncrystalline region is introduced on crystallizing the same polymer either by controlled synthesis or solution or melt. 2 H NMR combined with line shape simulations yield detailed information on the geometry and frequency of the segmental motion in the noncrystalline regions of deuterated UHMWPE crystallized at three different conditions. High resolution solid-state 13 C NMR reveals the temperature dependence of the conformation statistics of chain segments in the noncrystalline regions of the samples. Combining the observations from the 2 H and 13 C NMR, the influence of segmental motions on the conformation statistics in the noncrystalline regions of the samples are discussed.